"Damage Control" Fixation of Displaced Femoral Neck Fractures in High-Risk Elderly Patients: A Feasibility Case Series. Issue 12 (December 2021) - Konda, Sanjit R.; Dedhia, Nicket; Rettig, Samantha; Davidovitch, Roy; Ganta, Abhishek; Egol, Kenneth A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To assess the outcomes of patients who underwent closed reduction and percutaneous pinning (CRPP) with cannulated screws for treatment of a displaced femoral neck fracture (DFNF) as they were deemed too high risk to undergo hemiarthroplasty (HA). Design: Prospective cohort study. Setting: One urban academic medical center. Patients/Participants: Sixteen patients treated with CRPP and 32 risk-level–matched patients treated with HA. Intervention: CRPP for patients with DFNFs who were deemed too ill to undergo HA. The concept being that CRPP would aid in pain control and facilitate mobilization and if failed, the patient could return electively after medical optimization for conversion to arthroplasty. Main Outcome Measurements: Complications, readmissions, mortality, inpatient cost, and functional status. Results: The CRPP cohort had a greater incidence of exacerbations of chronic medical conditions or new onset of acute illness and an elevated mean American Society of Anesthesiologist score. There were no differences in discharge location, length of stay, major complication rate, ambulation before discharge, or 90-day readmission rate. Patients undergoing CRPP were less likely to experience minor complications including a significantly decreased incidence of acute blood loss anemia. Three patients (18.7%) in the CRPP cohort underwent conversion to HA or THA. There was no difference in inpatient, 30-day, or 1-year mortality. Conclusion: In the acutely ill patients with DFNFs, "damage control" fixation with CRPP can be safely performed in lieu of HA to stabilize the fracture in those unable to tolerate anesthesia or the sequelae of major surgery. Patients should be followed closely to evaluate the need for secondary surgery. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of Levels of Evidence.